2020
DOI: 10.7759/cureus.7078
|View full text |Cite
|
Sign up to set email alerts
|

Poll Everywhere to Encourage Learner Satisfaction and Participation in Internal Medicine Fellowship Didactics

Abstract: Active learning improves self-reported engagement and satisfaction in medical education. Audience response systems are one mechanism of encouraging participation, especially in a setting in which learners in varying educational levels are present. Three fellowships participated in this educational quality improvement project where Poll Everywhere® was incorporated into didactics. Attendees were invited to complete a 4-question retrospective prepost satisfaction survey. Incorporation of the Poll Everywhere® aud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 15 publications
(14 reference statements)
0
10
0
Order By: Relevance
“…Given the practicality issues with the classic ARS, newer alternatives such as “Poll everywhere ® ” have been successfully used in medical education. 13 , 20 , 21 Poll everywhere ® and similar polling software’s are affordable, more convenient in terms of set up, students can use their own mobiles instead of remotes. Other advantages poll everywhere ® is flexibility in terms of location, instructors can integrate active learning remotely using such technology.…”
Section: Discussionmentioning
confidence: 99%
“…Given the practicality issues with the classic ARS, newer alternatives such as “Poll everywhere ® ” have been successfully used in medical education. 13 , 20 , 21 Poll everywhere ® and similar polling software’s are affordable, more convenient in terms of set up, students can use their own mobiles instead of remotes. Other advantages poll everywhere ® is flexibility in terms of location, instructors can integrate active learning remotely using such technology.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 84 % of the participants found that Poll Everywhere sessions highlighted their strengths and weaknesses. Even for fellowship programs, as seen in Castillo et al (2020) study on the didactics of medicine fellowship, a significantly higher student satisfaction was obtained when Poll Everywhere was used. Histology, an image-intensive topic, is challenging for both learners and educators (Al Khader et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…There are ways to increase opportunities for engagement based on prior literature, including flipping the classroom. [10][11][12][13] We are working to address the challenge of limited interaction with tools such as online polling services, and the use of "breakout" rooms.…”
Section: Discussionmentioning
confidence: 99%